2008
DOI: 10.5897/ajb2008.000-5043
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the physicochemistry of a small tropical reservoir (Aiba Reservoir, Iwo, Osun, Nigeria)

Abstract: Aiba Reservoir was sampled between March, 2004 and February, 2005 for physico-chemical studies. Air temperatures ranged from 20.00-30.50 o C (mean ± s.e: 26.33 ± 0.26 o C), water temperature ranged from 25.00-35.00 o C (mean ± s.e: 29.26 ± 0.19 o C), pH ranged from 5.53-9.48 (mean ± s.e: 7.98 ± 0.11), dissolved oxygen ranged from 1.75-11.20 mgO 2 /l (mean ± s.e: 7.23 ± 0.20 mgO 2 /l), alkalinity ranged from 42.50-85.00 mg/l (mean ± s.e: 65.20 ± 0.85 mg/l), total hardness ranged from 12.00-59.00 mg/lCaCO 3 (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 11 publications
9
30
0
1
Order By: Relevance
“…pH was also highest (6.74) in February (scanty rain), and lowest (6.25) in August (Frequent rain) this could be due to high and low load of acid neutralizing particulates in the atmosphere that is washed down by the rain in the months respectively (Table 3). This result also agrees with Atobatele (2008) that pH decreases with increase in rainfall. In Table 3, all the major ionic concentrations were higher in dry season except for SO 4 2-and NO 3 -which are higher during wet season.…”
Section: Resultssupporting
confidence: 82%
“…pH was also highest (6.74) in February (scanty rain), and lowest (6.25) in August (Frequent rain) this could be due to high and low load of acid neutralizing particulates in the atmosphere that is washed down by the rain in the months respectively (Table 3). This result also agrees with Atobatele (2008) that pH decreases with increase in rainfall. In Table 3, all the major ionic concentrations were higher in dry season except for SO 4 2-and NO 3 -which are higher during wet season.…”
Section: Resultssupporting
confidence: 82%
“…In the present study, spatial variations among the investigated parameters were mostly statistically significant (p<0.05) except for transparency, temperature, pH, nitrite, phosphate, total solids, calcium, sodium, potassium and sulphate. According to Atobatele and Ugwumba [34] and Ayoade et al [35], these marked spatial variations may be related to patterns of water use, temperature and rainfall influx. In contrast, only pH, BOD, nitrite and total alkalinity showed non-significant (p>0.05) temporal vicissitudes, and this seasonal vagary pattern is common for most tropical inland ecosystems as a result of allochthonous run-off into river basins during the rainy season [34,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…While the reservoir was dominated by copepods [6], its receiving stream was dominated by rotifers [18]. Furthermore, while the previous physicochemical study of the reservoir indicated a healthy system [15], that of its outflowing stream indicated a stressed system [19]. Several studies have been carried out on the zooplankton fauna and water quality of Nigerian freshwaters, but such studies have always focused on reservoirs, lakes, and large rivers with no due attention on their headwater streams.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of headwater streams in freshwater systems cannot be overemphasized but is unfortunately often ignored in limnological studies. For instance, Aiba Reservoir has been copiously studied (e.g., [6,15,16]) but with little or no attention on its adjacent streams. Not until recently were studies carried out in the downstream section of the reservoir [17][18][19].…”
Section: Introductionmentioning
confidence: 99%